ELASTISITAS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KEBUTUHAN ANGKUTAN UMUM DI LONDON DAN YOGYAKARTA - Gito Sugiyanto; Sugiyanto Sugiyanto (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2009)
The aim of this study is to analyze the elasticity of factors which influence the demand of public transport in London and Yogyakarta, based on the study of Paulley et al (2006) and the study of Sugiyanto (2007). The mode choice model between private cars and public transport (city bus) was developed based on users preferences as indicated by travel attributes. Five travel attributes were assumed to have high influences toward mode choice behavior, i.e; travel cost, congestion charge, travel time, headway of public transport (city bus), and walking time to the bus stop. The logit binomial model was used to formulate the individual behavior based on the stated preference data obtained from private car users in the Malioboro corridor. Themode choice model between private cars and city bus was developed based on 520 options from 65 respondents who used private cars to go to Malioboro to be as through traffic. Based on the direct and cross elasticity, the travel cost attribute has the highest elasticity value. Travel cost is the most sensitive attributewhich influences the election probability of private cars and city bus. The factors which influence the demand of public transport in London are fares, quality of service, income, and car ownership.Keywords: mode choice, stated preference, and elasticity